Nationality, Gender, Age, and Body Mass Index Influences on Vitamin D Concentration among Elderly Patients and Young Iraqi and Jordanian in Jordan - Hanan Al-Horani; Wael Abu Dayyih; Eyad Mallah; Mohammed Hamad; Mohammad Mima; Riad Awad; Tawfiq Arafat (Biochemistry Research International)
Vitamin D is necessary for maintaining and regulating calcium levels; thus, insufficiency of vitamin D increases the risk of many chronic diseases. This study aimed to examine vitamin D levels among Jordanian and Iraqi volunteers and find the relation between vitamin D level and lipid profile patients. Vitamin D levels were evaluated using enzyme-linked immunosorbent assay. For young healthy group subjects, vitamin D levels were 20.60 ± 5.94 ng/mL for Jordanian and 27.59 ± 7.74 ng/mL for Iraqi. Vitamin D concentrations for young males and females were 25.82 ± 8.33 ng/mL and 21.95 ± 6.39 ng/mL, respectively. Females wearing hijab were 20.87 ± 6.45 ng/mL, while uncovered females were 23.55 ± 6.04 ng/mL. For >40 years Iraqi subjects, vitamin D level for healthy was 29.78 ± 9.49 ng/mL and 23.88 ± 7.93 ng/mL for hyperlipidemic subjects. Vitamin D levels for overweight and obese healthy groups were significantly higher (P<0.050) than those for the hyperlipidemic patients groups. Vitamin D levels for males were significantly higher than females and were significantly higher for healthy than those hyperlipidemic Iraqi patients. These findings showed that vitamin D levels are affected by age, nationality, gender, and health statues and highlight the importance of vitamin D supplementation for groups with low levels particularly old, hijab wearing females, and hyperlipidemic groups.